The arithmetic of Z-numbers theory and applications - Aliev, Rafik A; Huseynov, Oleg H; Aliyev, Rashad R; Alizadeh, Akif A (World Scientific, 2015)
Real-world information is imperfect and is usually described in natural language (NL). Moreover, this information is often partially reliable and a degree of reliability is also expressed in NL